2016
DOI: 10.1017/s0022149x16000699
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of the rumen flukes Paramphistomum leydeni and Paramphistomum cervi in a concurrent infection of the red deer Cervus elaphus

Abstract: Paramphistomosis, caused by paramphistomid flukes, is a gastrointestinal parasitic disease of domestic and wild ruminants. Originally thought to be limited to the tropics and subtropics, the disease has recently been reported in temperate regions. Here we describe the concurrent infection of a red deer doe (Cervus elaphus) with Paramphistomum leydeni and Paramphistomum cervi. This is the first report of P. leydeni in Croatia. Flukes were identified on the basis of morphological keys (tegumental papillae) and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The BLAST analysis of the obtained sequence revealed 100% similarity with P. cervi of China and 98% with P. epiclitum and other Paramphistomum species of India indicating the common phylogenetic history owing to the results of a previous study [25,29]. This similarity may be due to the fact that these areas are neighboring to Pakistan and sharing the same geographical, environmental conditions with free movement of infected hosts.…”
Section: Discussionmentioning
confidence: 67%
“…The BLAST analysis of the obtained sequence revealed 100% similarity with P. cervi of China and 98% with P. epiclitum and other Paramphistomum species of India indicating the common phylogenetic history owing to the results of a previous study [25,29]. This similarity may be due to the fact that these areas are neighboring to Pakistan and sharing the same geographical, environmental conditions with free movement of infected hosts.…”
Section: Discussionmentioning
confidence: 67%
“…In the past, the histomorphological examination of fluke specimens of bovine origin from Germany led to a controversial interpretation with respect to the identification of P. leydeni , which was considered synonymous with P. cervi by some authors (Odening et al 1978 ; Eduardo 1982 ; Odening 1983 ). Using molecular diagnosis, P. leydeni has been identified parasitizing cervids in Europe in the recent past, including one case of co-infection with P. cervi (O’Toole et al 2014 ; Sindičić et al 2017 ), but was occasionally identified from fluke eggs excreted by sheep and cattle in Ireland and the Netherlands, respectively (Martinez-Ibeas et al 2016 ; Ploeger et al 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Paramhistomum parasites collected from a reindeer in Croatia reported P.cervi and P. leydeni as a result of sequence analysis conducted in the rDNA ITS-2 gene region by molecular methods (23). Sanabria et al (19) Paramphistomum leydeni was identified molecular using 5.8S and 28S partial ITS-2 rDNA sequences.…”
Section: Discussionmentioning
confidence: 99%